2020
DOI: 10.3390/agronomy10060890
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Assessment in Agricultural Soil Potentially Contaminated by Geogenic Thallium: Influence of Plant Species on Metal Mobility in Soil-Plant System

Abstract: In agricultural soils, thallium (Tl) of geogenic origin may represent a potential risk for human health, mainly via ingestion of food crops. In this work, a pot experiment was carried out to evaluate (1) the bioavailability of Tl and other potentially toxic elements (PTEs) in an agricultural soil with naturally occurring Tl; (2) the uptake and accumulation of PTEs in Lactuca sativa L. var. acephala, Diplotaxis tenuifolia L. DC and Silene latifolia Poir; (3) the health risks arising from plant and soil ingestio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…Depending on soil type, CB is able to remove 5900 g•ha −1 of Cu in Inceptisol and 3052 g•ha −1 in Mollisol, with root copper concentration 90 times higher than that in leaves and stems [55]. Castor bean plants exhibit a bioconcentration factor (BCF, a ratio of element concentration in the plant shoots to element concentration in the soil [172,174,176]) and translocation factor (TF, ratio of element concentration in shoots and roots [177,178]) <1, indicating that CB is not a Cu accumulator plant and is well suited for phytostabilization due its low metal transfer rate [35,55,179]. Copper accumulation in CB seems to be directly related to phosphorous content in soils [35].…”
Section: Phytoremediation Potentialmentioning
confidence: 99%
“…Depending on soil type, CB is able to remove 5900 g•ha −1 of Cu in Inceptisol and 3052 g•ha −1 in Mollisol, with root copper concentration 90 times higher than that in leaves and stems [55]. Castor bean plants exhibit a bioconcentration factor (BCF, a ratio of element concentration in the plant shoots to element concentration in the soil [172,174,176]) and translocation factor (TF, ratio of element concentration in shoots and roots [177,178]) <1, indicating that CB is not a Cu accumulator plant and is well suited for phytostabilization due its low metal transfer rate [35,55,179]. Copper accumulation in CB seems to be directly related to phosphorous content in soils [35].…”
Section: Phytoremediation Potentialmentioning
confidence: 99%
“…Both the grass swards reported a significant positive correlation between NH 4 NO 3 -extractable concentration of Pb in the soil and Pb concentration in plant shoots, revealing that the readily bioavailable content of PTEs in the soil are generally related to the amounts taken up by the plants [68] (Tables 5 and 6). Furthermore, a negative correlation was observed for both the grass swards between pore water pH and Cd concentration in pore water.…”
Section: Correlations Between Plant and Soil Propertiesmentioning
confidence: 94%
“…According to the very high pseudototal concentrations of Cd and Pb in the studied soil, the NH 4 NO 3 -extractable concentrations of Cd and Pb for both the grass swards were above the trigger values (0.1 mg kg −1 for Cd and 0.1 mg kg −1 for Pb) settled by some European countries for contaminated soil in order to identify potential risks for the environment and plant growth [49][50][51]67,68] (Table 2).…”
Section: Soil Mineral Nitrogen and Pte Promptly Bioavailable Concentrationsmentioning
confidence: 99%
“…Likewise, the level of cadmium (Appendix A-Tables A1 and A2), also exceeded the minimum values established by the regulations for water for human consumption; studies have been reported where the exposure of L. sativa to this metal causes toxic and harmful effects that decrease its growth as the concentration of Cd, and thereby its adsorption, increases [59][60][61]. Just as the presence of heavy metals and cyanide has toxic implications in the plant and animal model, in the same way, it will affect the health of the human being [62,63].…”
Section: Lactuca Sativamentioning
confidence: 94%